VALUASI TINGKAT KESEHATAN PADA KOPERASI KREDIT BINTANG TIMUR JAWA TIMUR MENGGUNAKAN CAMEL - Mayasari, Dewi; Masrunik, Endah; Huda, Anam Miftakhul; Elvianita, Diana (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
This research aims to level of Credit Union Bintang Timur health by using CAMEL method during a period of time of 2017. CAMEL method has five aspects, which are Capital Adequacy Ratio (CAR), earning asset quality ratio (KAP), management, asset earning power and liquidity loan to deposit ratio. The results and discussion of all CAMEL factors in the category "Fairly Healthy" except on the quality factor of productive assets and management, Productivity asset quality ratio and management are categorized "Not Healthy" due to too high bad loans and too many expenses incurred. Conclusions and suggestions based on the CAMEL method states the health status of the year 2017 gets the predicate "Fairly Healthy" because it scores 67.79% that is in the range of 66-81.